Integrated Analysis Reveals That miR-193b, miR-671, and TREM-1 Correlate With a Good Response to Treatment of Human Localized Cutaneous Leishmaniasis Caused by Leishmania braziliensis - Nunes, Sara; Silva, Icaro Bonyek; Ampuero, Mariana Rosa; Noronha, Almério Libório Lopes de; Souza, Lígia Correia Lima de; Correia, Thaizza Cavalcante; Khouri, Ricardo; Boaventura, Viviane Sampaio; Barral, Aldina; Ramos, Pablo Ivan Pereira; Brodskyn, Cláudia; Oliveira, Pablo Rafael Silveira; et al. (Frontiers in Immunology, 2018)
Localized Cutaneous Leishmaniasis (LCL) is a chronic disease characterized by ulcerated skin lesion(s) and uncontrolled inflammation. The mechanisms underlying its pathogenesis are not completely understood and little is known about posttranscriptional regulation during LCL. MicroRNAs (miRNAs) are non-coding small RNAs that regulates gene expression, which can be implicated in the pathogenesis of LCL. Then, we investigated the involvement of miRNAs and their targets genes in human LCL using publicly available transcriptome data sets, followed by ex vivo validation. Initial analysis highlighted that miRNAs expression is altered during LCL, clustering patients separately from controls. Joint analysis identified 8 high confidence miRNAs altered (-1.5≤fold change≥1.5; p<0.05) between cutaneous ulcers and uninfected skin. We found that the expression of miR-193b and miR-671 are greatly associated with their target genes, CD40 and TNFR, indicating an important role of these miRNAs in the expression of genes related to the inflammatory response observed in LCL. Besides, network analysis revealed that, miR-193b, miR-671 and TREM1 correlate only in patients that shows faster wound healing (up to 59 days) than in patients with longer time of cure (more than 60 days). Given that these miRNAs are associated with the control of inflammation and time of healing, our findings reveal that they might influence the pathogenesis and prognosis of LCL.